2021
DOI: 10.1038/s42004-021-00588-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic zwitterions as efficient non-permeable cryoprotectants

Abstract: Cryopreservation of cells is necessary for long periods of storage. However, some cell lines cannot be efficiently cryopreserved, even when optimized commercial cryoprotectants are employed. Previously, we found that a low-toxic synthetic zwitterion aqueous solution enabled good cryopreservation. However, this zwitterion solution could not cryopreserve some cells, such as human kidney BOSC cells, with good efficiency. Therefore, details of the cryoprotective effect of the zwitterions and optimization based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(56 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…r air air air solution solution solution (10) where α i can be calculated by summarizing the absorption of loaded nanoparticles and cell medium solvent from eq 11 as…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…r air air air solution solution solution (10) where α i can be calculated by summarizing the absorption of loaded nanoparticles and cell medium solvent from eq 11 as…”
Section: ■ Methodsmentioning
confidence: 99%
“…Cell freezing techniques are used to preserve cells with cryoprotectants below the freezing point. However, cell resuscitation still remains a challenge due to the low cell viability after the thawing process. ,, The traditional water bath recovery method often leads to ice recrystallization of cell sap near the equilibrium point, and the cell will be dehydrated during its resuscitation process. Although studies have shown that certain types of cell preservation medium are helpful in cryopreservation, in order to obtain a satisfying survival rate of cells, high temperature elevation rate should be applied to escape the recrystallization zone. ,, …”
Section: Introductionmentioning
confidence: 99%
“…[28,29] Therefore, an electron-withdrawing zwitterionic unit called 3-(2-methylquinolin-1-ium-1-yl) propane-1-sulfonate (SQ) was introduced to confer these probes' cell impermeability (Figure 1a). [30,31] The detailed synthesis was given in the Supporting information and Figures S1-S10, Supporting Information.…”
Section: Molecular Design and Photophysical Propertiesmentioning
confidence: 99%
“…18,19,21 We also have reported that the cell toxicity of articial ZIs is lower than that of dimethyl sulfoxide, which is generally used for biological and medical research, and can be used for cryostorage of animal cells. 22,23 Therefore, we hypothesised that ZIs have protein-stabilizing potential under cryostorage of unstable proteins, especially GnT-V.…”
mentioning
confidence: 99%
“…1), which exhibits enzyme compatibility and the cryoprotective ability for cells. 20,22,23 Two more articial ZIs, VimC 3 S and C 1 imC 3 S, 23 were also utilised to investigate the effect of different zwitterionic structures on the ability (Fig. 1), because additional ZIs can be synthesised at a lower cost than expensive OE 2 imC 3 C. 24 Fig.…”
mentioning
confidence: 99%